Kinetika Reaksi Sintesis Magnetite Menggunakan Metode Kopresipitasi Dengan Pendekatan Model Avrami - Adela Shofia Addabsi; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Magnetite is a material that can be used in a drug delivery aplication. The purpose of this study is to determine the effect of temperature and stirring rate on the magnetite crystal size and determine the kinetic equation of magnetite synthesis with Avrami model approach. The magnetite was synthesized using coprecipitation method by reacting FeCl3 and FeCl2 in 2:1 mole ratio and NH4OH 10% at temperature range of 40°C, 60°C, 80°C, and a stirring rate were 300, 400, 500 rpm in a beaker. Samples were taken about 20 mL in every 5 minutes for 30 minutes. Then the sample was filtered to separate solids and filtrate. Analysis of Fe concentrations in the filtrate was using AAS, while the precipitate was washed until neutral and dried at 100°C for 2 hours. Then the magnetite powder was characterized by XRD and SEM-EDX. From the characterization we found a cubic structure of magnetite and crystals size of magnetite is about 10-12 nm formed. The morphology of the magnetite particles tended to be aglomerated but if the temperature and stirring rate increased, the aglomeration of the particles would be uniform. This synthesis of the magnetite could be approximated by the Avrami model with the core of forming function value (n) is ranging from 1.3-1.6. If the temperature and the stirring rate increased, the value of the rate constant of transformation (k) increased too. At temperature 30 °C; 300 rpm obtained the constant rate of transformation of 0.01 min-1 and 0.08 min-1 at temperature 80 °C; 500 rpm.Keywords: aglomeration, avrami, coprecipitation, drug delivery, magnetite